2019
DOI: 10.1002/ijc.32553
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term status of predicted body fat percentage, body mass index and other anthropometric factors with risk of colorectal carcinoma: Two large prospective cohort studies in the US

Abstract: Anthropometric measurements, such as body mass index (BMI), waist circumference, and body fat percentage, have been used as indicators of obesity. Despite evidence that excess body fat is a risk factor for colorectal carcinoma (CRC), the magnitude of the association of BMI and other obesity indicators with the long‐term risk of CRC remains unclear. Utilizing a Cox proportional hazards regression model, we examined differential associations between predicted body fat percentage and BMI with the risk of CRC (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“… 125 However, the study by Hanyuda et al. 126 found that the percentage of body fat was quite positively correlated with CRC mortality, which is inconsistent with the finding that ‘overweight is a good protective factor for survival in CRC’ in our study. This suggests that there may be differences in the effects of different obesity indicators on CRC progression, and further exploratory studies are needed in the future.…”
Section: Discussioncontrasting
confidence: 99%
“… 125 However, the study by Hanyuda et al. 126 found that the percentage of body fat was quite positively correlated with CRC mortality, which is inconsistent with the finding that ‘overweight is a good protective factor for survival in CRC’ in our study. This suggests that there may be differences in the effects of different obesity indicators on CRC progression, and further exploratory studies are needed in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…Other interesting findings are related to the analysis of the correlation between anthropometric measures, lifestyle and gender differences with the presence of adenomas at endoscopy. Although many reports show that excess body fat is a risk factor for colorectal cancer, the extent of the association of BMI and other indicators of overweight with long-term risk of CRC remains unclear [46]. The data collected did not show a statistically significant correlation between waist circumference, waist-to-hip ratio (used as an indicator of central adiposity), BMI and the presence of adenomas.…”
Section: Discussionmentioning
confidence: 77%
“…Clinicians have long been using BMI as a proxy measure for adiposity and screener for cardiometabolic risk [ 43 ]. Our results do not support the routine use of BMI for this aim, considering the more reliable indices that we have identified, especially since BMI does not account for muscle mass nor does it identify whether excess fat is accumulating in the abdominal region [ 44 ].…”
Section: Discussionmentioning
confidence: 99%